In vitro and in vivo evaluation of antagonistic potential of fungal and bacterial bioagents against Macrophomina phaseolina causing dry root rot in Clusterbean - S. GANGOPADHYAY, ANAND KUMAR MEENA* and (Indian Phytopathology, 2016)
Antagonistic potentiality of twelve fungal and ten bacterial antagonists was evaluated against Macrophomina phaseolina under laboratory condition. Besides, the mechanism of action of bioagents in suppressing the growth of Macrophomina phaseolina was seen. The disease control efficacy of five fungal and bacterial bioagents used alone and in combination as seed treatment (ST), soil application(SA) and both ST+SA against root rot in clusterbean was studied under artificial soil inoculation condition in green house. Fungal antagonist T. viride (Tv-BKN) and bacterial antagonist P. fluorescens (Pf-18) were significantly inhibited the mycelial growth of M. phaseolina in vitro. The application of bioagents through seed and soil together provided better control as compare to their use as either seed or soil treatment. The root rot incidence was less in combined bioagents i.e. T. viride (Tv-BKN) and P. fluorescens (Pf-18).